Resistance to Fracture of Zirconia Abutments with Different Angulations: Impact of Implant Platform Diameter - Saker, Samah; AL-Zordk, Walid; Özcan, Mutlu (European Journal of Dentistry, 2020)
Objective The aim of this study was to assess the impact of implant platform diameters on ultimate force to failure of zirconia abutments with different angulation.Materials and Methods Forty-two zirconia abutments with either 0 degree (ST) or 15-degree (AN) angulation were assembled on tapered internal connection titanium implants (Direct's Legacy; 13 mm Implant Direct, LLC, Las Vegas, United States) with a platform diameter of Ø3.0, Ø3.5, and Ø4.5 mm (14 per group). Zirconia crowns (Ceramill Zolid; Amann Girrbach GmbH) were fabricated and cemented using self-adhesive resin cement (MaxCem Elite, Kerr). The specimens were thermomechanically loaded (TCML= 6,000 cycles of 5 to 50°C for 2 minutes/cycle followed by cyclic loading 600,000 cycles) followed by static loading until fracture. The data of load (N) at which fracture occurred were statistically analyzed by using Kruskal–Wallis analysis of variance and Mann–Whitney U tests at 5% significance level.Results Higher load to fracture was reported for zirconia crowns in straight abutments groups and a platform of 4.5, 3.5, and 3 mm diameter was 438.2± 85.4, 345.5± 71.3, and 331.1± 59.1 N, respectively. However, the groups restored with zirconia crowns in angulated abutments groups and a platform of 4.5, 3.5, or 3 mm diameter showed a fracture load of 411.4 ± 49.8, 354.2 ± 52.5, and 302.8 ± 52.5 N, respectively.Conclusion Straight and angulated zirconia abutments presented similar load to fracture on 3 and 3.5 mm platform diameters yet being significantly less for 4.5 mm diameter.
Keywords: zirconia abutment; fracture resistance; abutment angulations; implant diameters